Hustle Culture: A New Face of Slavery - Mutiah Nabilla Ulfah; Muhamad Fadhil Nurdin (Aliansi, 2022)
This article offers a critical examination of the emergence of the hustle culture phenomenon happening to freelance workers in Indonesia, most of whom are millennials and generation Z. It argues that there is the situation of unequal power relations between workers and owners of capital in the form of exploitation through hustle culture that promotes the discourse of being productive by working non-stop. The workers are unconsciously carried away by the hustle culture which affects their well-being. It proposed that complex working relationships between capitalists and workers become more complicated to define because of the growing gig economy. The discussion about well-being of freelance workers and the hustle culture draws by using a literature study supported by secondary data. Furthermore, to deepen the analysis, the discussion is studied by developing a new synthesis to Karl Marx's theory of capitalism and labor exploitation and the theory of agent and structure by Anthony Giddens. This synthesis leads to strengthen Giddens's critique of Marx which ignores the knowledgeability and competence of actors; they must be built around a concept of the 'duality of structure', in which social structures are viewed as both the medium and outcome of the practices which constitute social systems. Workers are the agents of development of large industries and they have the power to control their rights and obligations. This also aims to develop a new understanding in the field of industrial sociology and share an expanded evaluative framework to inform local, national, and international worker policy and practice.